'We are the people': Framing the notion of the people in the Egyptian revolutionary context. Issue 1 (1st January 2021) - Diana, Chiara; Steuer, Clément
ABSTRACT: The long dismissed notion of the people has recently generated much interest in academic literature. Understood as an "emotional community", the people has been returned to centre stage physically and symbolically by the emblematic slogan "The people want the fall of the regime", during the Arab Spring. This themed issue investigates not only the heuristic interest of the notion of the people but also its multifaceted development in the revolutionary Egypt. Specifically, the authors explore the construction of the people's legitimacy through revolutionary slogans, the emergence of the political subjectivity of child martyrs, and the way in which political actors used this notion during the 2011 elections.